Wired for behaviors: from development to function of innate limbic system circuitry - Sokolowski, Katie; Corbin, Joshua G. (Frontiers in Molecular Neuroscience, 2012)
The limbic system of the brain regulates a number of behaviors that are essential for the survival of all vertebrate species including humans. The limbic system predominantly controls appropriate responses to stimuli with social, emotional or motivational salience, which includes innate behaviors such as mating, aggression and defense. Activation of circuits regulating these innate behaviors begins in the periphery with sensory stimulation (primarily via the olfactory system in rodents), and is then processed in the brain by a set of delineated structures that primarily includes the amygdala and hypothalamus. While the basic neuroanatomy of these connections is well established, much remains unknown about how information is processed within innate circuits and how genetic hierarchies regulate development and function of these circuits. Utilizing innovative technologies including channel rhodopsin-based circuit manipulation and genetic manipulation in rodents, recent studies have begun to answer these central questions. In this article we review the current understanding of how limbic circuits regulate sexually dimorphism and how these circuits are established and shaped during pre- and post-natal development. We also discuss how understanding developmental processes of innate circuit formation may inform behavioral alterations observed in neurodevelopmental disorders, such as autism spectrum disorders, which are characterized by limbic system dysfunction.